2013
DOI: 10.1364/oe.21.009103
|View full text |Cite
|
Sign up to set email alerts
|

Experimental performance of DWDM quadruple Vernier racetrack resonators

Abstract: We demonstrate that one can meet numerous commercial requirements for filters used in dense wavelength-division multiplexing applications using quadruple Vernier racetrack resonators in the silicon-on-insulator platform. Experimental performance shows a ripple of 0.2 dB, an interstitial peak suppression of 39.7 dB, an adjacent channel isolation of 37.2 dB, an express channel isolation of 10.2 dB, and a free spectral range of 37.52 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Finally, it is worth specifying that the ultrafast all-optical tuning demonstrated here can be employed in Vernier devices with multiple cascaded ring or racetrack resonators designed to operate in the first regime of the Vernier effect, where FSRs larger than 95 nm [40,44] as well as interstitial peak suppressions up to 40 dB [45] can be achieved for ultra-high performance optical filtering.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is worth specifying that the ultrafast all-optical tuning demonstrated here can be employed in Vernier devices with multiple cascaded ring or racetrack resonators designed to operate in the first regime of the Vernier effect, where FSRs larger than 95 nm [40,44] as well as interstitial peak suppressions up to 40 dB [45] can be achieved for ultra-high performance optical filtering.…”
Section: Resultsmentioning
confidence: 99%
“…Ring resonator-based filters have been shown to meet numerous commercial specifications. Popović et al, for example, showed that telecom specifications can be met using four series-coupled silicon microring resonators (MRRs) [5] and Boeck et al have shown that many key commercial specifications for adding or dropping signals can be met using silicon quadruple series-coupled Vernier racetrack resonators [6]. However, ring resonators have free spectral ranges (FSRs) that limit the number of channels that can be used; thus, it is desirable to have a large FSR to have a large number of usable channels [4].…”
mentioning
confidence: 99%
“…L a;b;c;d are the total lengths of the racetrack resonators, κ 1 and κ 5 are the symmetric (real) point field coupling factors to the bus waveguides, κ 2;3;4 are the inter-ring symmetric (real) point field coupling factors, and t 1;2;3;4;5 are the respective (real) point field transmission factors. The derivations of the transfer functions can be found in [13,16]. The following simulations assume that L a L b 2πr 2L x (where r 5 μm and L x 7 μm), L c L d 4∕3L a 2πr 2L x 2L (where L 7.569 μm), κ 1 κ 5 , κ 2 κ 4 , t 1 t 5 , and t 2 t 4 .…”
mentioning
confidence: 99%
“…The schematic of the quadruple Vernier racetrack resonator is shown in Fig. 1(a), which has an asymmetric arrangement of resonators as described in [10][11][12]16]. The fabricated device is shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation